A global history of modern historiography - Iggers, Georg G. 1926-2017; Wang, Q. Edward 1958-; Mukherjee, Supriya (Routledge, Taylor & Francis Group, 2017)
"Looks not just at developments in the West but also at the other great historiographical traditions in Asia, the Middle East, and elsewhere in the non-Western world over the course of the past two and a half centuries"...Provided by the publisher
Includes bibliographical references and index
Keywords: Geschichte 1700-2016; Geschichte 1700-2007; Geschichte 1750-2012; Geschichte; Historiography -- History; Geschichtsschreibung; Aufsatzsammlung